Analysis of air pollutants source using descriptive method - Zahari N.M.; Mahran R.M.S.; Zawawi M.H.; Nazmi I.; Rasdan M.I.; Agusril; Abas A. (American Institute of Physics Inc., 2023)
The air pollutants and meteorological parameters are sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), ozone (O3), and particulate matter (PM10). The selected locations are Melaka (Station 1), Kelang, Nilai, Shah Alam, Melaka (Station 2) and Putrajaya for year 2009 until 2015. This study is to analyze the air pollutant sources using descriptive analysis and determine the relationship between the air pollutants parameters. The data was obtained from the Department of Environment Malaysia (DOE). The software used was Statistical Package for Social Science (SPSS) in order to do the analysis which are the descriptive analysis, correlation and principle component analysis. The function of descriptive analysis is to find the value of minimum, maximum, range, mean, standard deviation and variance of the air pollutant parameters. 2019 Author(s).